2016
DOI: 10.1111/jora.12258
|View full text |Cite
|
Sign up to set email alerts
|

Part‐Time Employment and Problem Behaviors: Evidence From Adolescents in South Korea

Abstract: This study explores the impact of adolescent part-time work experience on problem behaviors in the South Korean context. To achieve this, propensity score matching (PSM) analyses were employed based on data from the Korean Education Employment Panel (KEEP). Results indicate that adolescents' part-time employment during their secondary school years had significantly undesirable effects on drinking and smoking, even after preexisting differences between the two groups (i.e., those adolescents who participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
2
8
0
Order By: Relevance
“…Also, adolescents with part-time job experience had more than three times higher rates of drinking experience, binge drinking, smoking experience, and sexual experience than those without part-time work experience. These results are consistent with Lee’s finding [ 9 ] that middle school students with part-time jobs have higher drinking and smoking rates. In general, the relationship between adolescents’ part-time work experience and delinquency can be explained by the theory of differential socialization [ 9 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, adolescents with part-time job experience had more than three times higher rates of drinking experience, binge drinking, smoking experience, and sexual experience than those without part-time work experience. These results are consistent with Lee’s finding [ 9 ] that middle school students with part-time jobs have higher drinking and smoking rates. In general, the relationship between adolescents’ part-time work experience and delinquency can be explained by the theory of differential socialization [ 9 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, steady work for low-income adolescents is associated with a more positive view of the future and higher efficacy [ 6 ]. On the other hand, youth employment has been associated with low academic achievement, misconduct, and suicidal thoughts [ 7 , 8 , 9 ]. In an American study, adolescents working more than 20 h a week had lower academic performance than those who worked fewer hours or those who did not work [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies have found an association between part-time work and problem behaviors among Korean adolescents, such as substance abuse, delinquency, and poor school adaptation [39,40]. Similarly, part-time work may adversely influence an adolescent’s peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In research on adolescent work and its effects on schooling, fulltime, but not part-time, work affects school enrollment and engagement adversely (13)(14)(15)). In addition, in studies of adolescent work, full-time work is associated positively with fertility and substance abuse (13,16,17), with some studies finding these effects only for White and economically advantaged youth (18). The few studies of minimum wage increases and adolescent schooling yield mixed results.…”
Section: Adolescent Workersmentioning
confidence: 99%